2006
DOI: 10.1111/j.2006.0030-1299.14209.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing lawns contribute to the subsistence of mesoherbivores on dystrophic savannas

Abstract: Resource manipulation, such as the creation and maintenance of grazing lawns, may shape the structure of herbivore communities. We tested the hypothesis that grazing lawns contribute towards the subsistence of the Kobus kob kob in a dystrophic West African savanna, where kob and Hippopotamus amphibius both occur. Comparison of the foliage of grazing lawns and ungrazed swards shows that hippo lawns are more nutritious with regard to both structure and nutrients; kob lawns are higher in nutrients only. Up to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 28 publications
1
114
1
Order By: Relevance
“…However, the evidence for facilitation in ungulate communities due to increased resource access through removal of obstructing grass parts during the dormant season is weak (Arsenault & Owen-Smith 2002). Although grazing facilitation in Bénoué N. P. is an important mechanism in ungulate communities during the wet season (Verweij et al 2006), we found no indication of grazing facilitation on unburned sites during the dry season when grasses are dormant. Instead, it is more likely that the aggregated co-occurrence patterns on unburned sites resulted from the use of patches of tall and dense grass by several species as escape cover to avoid predation (Moe et al 1990).…”
Section: Co-occurrence Patternscontrasting
confidence: 58%
“…However, the evidence for facilitation in ungulate communities due to increased resource access through removal of obstructing grass parts during the dormant season is weak (Arsenault & Owen-Smith 2002). Although grazing facilitation in Bénoué N. P. is an important mechanism in ungulate communities during the wet season (Verweij et al 2006), we found no indication of grazing facilitation on unburned sites during the dry season when grasses are dormant. Instead, it is more likely that the aggregated co-occurrence patterns on unburned sites resulted from the use of patches of tall and dense grass by several species as escape cover to avoid predation (Moe et al 1990).…”
Section: Co-occurrence Patternscontrasting
confidence: 58%
“…We postulate that the effects of shifting mosaics of grazing lawns maintained by hippos improve the quality of available forage close to water, which attracts herbivores in the MMNR riparian-edge habitats (McNaughton 1983;OwenSmith 1988;Fryxell 1991;Eltringham 1999;Adler et al 2001;Olff et al 2002;Arsenault and Owen-Smith 2002;Verweij et al 2006;Van Wieren and Bakker 2008). In contrast, the intense and homogeneous livestock grazing in the pastoral ranches limits forage intake by herbivores (Arsenault and Owen-Smith 2002;Verweij et al 2006), and repels herbivores from water points. Ultimately, continued sedentarization of pastoralists in the Mara region will progressively exclude herbivores and other wildlife from the pastoral areas of the Mara, similar to patterns reported for other parts of Masailand (Western et al 2009;Msoffe et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In diverse herbivore communities, the existence and strength of facilitation can determine the net effect of cattle and wildlife on one another and hence are important to long-term cattle-wildlife coexistence. Facilitation of forage quality or accessibility is usually defined as a short-term effect that bulk-feeding herbivores can have on forage for smaller herbivores (Bell, 1971;Gordon, 1988;Verweij et al, 2006). Facilitation through habitat modification involves long-term effects of different herbivore species on soil nutrient distribution and plant community composition (Arsenault and Owen-Smith, 2002).…”
Section: Introductionmentioning
confidence: 99%